Being Young in the Age of Globalization: A Look at Recent Literature on Neoliberalism's Effects on Youth - Turner, Justin (Social justice, 2014)
The article discusses various research studies and reports which address neoliberalism's effects on youth as of 2015, and it mentions the concept of being young in the age of globalization, as well as information about the number of children who live in poverty around the world. The economic, social, and cultural impacts of neoliberalism and youth crime are examined, along with juvenile justice and the work of social justice organizations.